Creativity in Malay commentary works: a special reference to Shaykh Dawud al-Fatani’s Ward al-Zawāhir = Kreativiti dalam komentari melayu: satu kajian terhadap karya Shaykh Dawud al Fatani, Ward al zawahir - Jusoh, Che' Razi (IIUM Press, International Islamic University Malaysia, 2017)
For generations, Dawud al-Fatani’s works have been considered among the reputable and reliable references in the literature of the Malay Archipelago. Among his authoritative works are: Munyat al-MusallÊ, Durr al-ThamÊn, FurË’ al-Masa’il, Minhaj al-‘Óbidin and al-Manhal al-Safi which have been praised for their lucid exposition of the issues addressed by al-Fatani in his writing. The hallmark of his scholarship is undoubtably his creativity and innovation, representing a key characteristic of the Islamic literature of the era and showcasing his gift for elucidating the primary texts of al-Qur’an and al-Hadith. This paper attempts to illustrate al-Fatani’s unique approach employed in his magnificent work entitled Ward al-Zawahir. The research reveals that among the techniques used by al-Fatani to enhance his writing, and which contributed so much to the Malay classical literature of the times are: Bilingualism, faedah (benefit point) and tanbih (admonishing point) etc. This paper is an exposure to the works of al-Fatani that will certainly benefit new generations of authors, enabling them to appreciate and draw inspiration from the literary heritage left to them by their predecessors.